2022
DOI: 10.1186/s13054-022-04061-6
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular lung water levels are associated with mortality: a systematic review and meta-analysis

Abstract: Background The prognostic value of extravascular lung water (EVLW) measured by transpulmonary thermodilution (TPTD) in critically ill patients is debated. We performed a systematic review and meta-analysis of studies assessing the effects of TPTD-estimated EVLW on mortality in critically ill patients. Methods Cohort studies published in English from Embase, MEDLINE, and the Cochrane Database of Systematic Reviews from 1960 to 1 June 2021 were syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Recent literature contributed to the indirect validation of the TPTD-derived estimation of lung water and permeability. A recent metaanalysis highlighted that extravascular lung water is associated with mortality in critically ill patients [35], confirming its physiological value. Pulmonary permeability estimated by TPTD has also been investigated by an animal study showing its ability to detect the elevation of inflammatory cytokines during acute respiratory distress syndrome (ARDS) [36].…”
Section: Sophisticated or Advanced Monitoring Systems: Transpulmonary...mentioning
confidence: 93%
“…Recent literature contributed to the indirect validation of the TPTD-derived estimation of lung water and permeability. A recent metaanalysis highlighted that extravascular lung water is associated with mortality in critically ill patients [35], confirming its physiological value. Pulmonary permeability estimated by TPTD has also been investigated by an animal study showing its ability to detect the elevation of inflammatory cytokines during acute respiratory distress syndrome (ARDS) [36].…”
Section: Sophisticated or Advanced Monitoring Systems: Transpulmonary...mentioning
confidence: 93%
“…Among more invasive diagnostic tools, the use of transpulmonary thermodilution not only presents an approach for hemodynamic monitoring, but also to approximate a patient’s fluid status [ 166 ]. Extravascular lung water is defined as the fluid volume outside the pulmonary vasculature, within the interstitial and alveolar spaces [ 166 , 167 ]. It was previously validated against the reference method of gravimetry in autopsy studies [ 167 169 ].…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Transpulmonary thermodilution (e.g., with use of the PiCCO™ system) and can be helpful in bedside clinical diagnosis and decision-making. It has been observed that an elevated extravascular lung water is linked to a higher mortality risk in ICU patients [ 166 ]. This association held true for both acute respiratory distress syndrome patients and critically ill patients without acute respiratory distress syndrome, suggesting the broad applicability of extravascular lung water as an indicator of disease severity [ 166 ].…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Intravenous fluid (IVF) administration has long been termed the 'cornerstone of resuscitation' (60). EGDT targeting a specific CVP (>8 mmHg) to guide fluid administration was initially thought to improve survival outcomes in patients with severe sepsis but studies found that only about 50% of these patients were fluid responders (61).…”
Section: Predictors Of Fluid Responsivenessmentioning
confidence: 99%